Peran Japesda dalam Penguatan Kebijakan Konservasi Lingkungan Berdasarkan Undang-Undang Republik Indonesia Nomor 32 Tahun 2024 (International Forum of Researchers and Lecturers, 2024)
This study examines Japesda's role in supporting the implementation of Law No. 32 of 2024 on the Conservation of Biological Natural Resources and Their Ecosystems. Japesda plays a strategic role in education and counseling, aligning with Article 37 paragraph (2), which mandates fostering public awareness through conservation education. It also contributes to managing conservation areas, as outlined in Article 5A and Article 8 paragraph (4), which emphasize local wisdom and participatory mapping. Japesda’s policy advocacy encourages community participation, supporting Article 37 paragraph (1), which underscores dialogue between the government, indigenous peoples, and stakeholders. Japesda is also active in monitoring and reporting violations, leveraging Article 39A paragraph (1), which recognizes community reports as valid initial evidence. Furthermore, Article 43A paragraph (1) provides a legal framework for Japesda to ensure conservation policies adhere to conservation principles. Despite challenges such as stakeholder resistance, limited resources, and low public awareness, Japesda continues to build capacity, forge partnerships, and enhance coordination among stakeholders. These efforts aim to overcome obstacles and support the effective implementation of conservation policies, ensuring the preservation of biological resources and their ecosystems for future generations. Japesda’s multifaceted role highlights its significance in advancing Indonesia's conservation agenda.